Deficient supplies of drugs for life threatening diseases in an African community - Andrew Marit; Lufesi Norman N; Aursnes Ivar (BMC, 2007)
Abstract Background In Malawi essential drugs are provided free of charge to patients at all public health facilities in order to ensure equitable access to health care. The country thereby spends about 30% of the national health budget on drugs. In order to investigate the level of drug shortages and eventually find the reasons for the drugs shortages in Malawi, we studied the management of the drug supplies for common and life threatening diseases such as pneumonia and malaria in a random selection of health centres. Methods In July and August 2005 we visited eight out of a total of 37 health centres chosen at random in the Lilongwe District, Malawi. We recorded the logistics of eight essential and widely used drugs which according to the treatment guidelines should be available at all health centres. Five drugs are used regularly to treat pneumonia and three others to treat acute malaria. Out-of-stock situations in the course of one year were recorded retrospectively. We compared the quantity of each drug recorded on the Stock Cards with the actual stock of the drug on the shelves at the time of audit. We reviewed 8,968 Patient Records containing information on type and amount of drugs prescribed during one month. Results On average, drugs for treating pneumonia were out of stock for six months during one year of observation (median value 167 days); anti-malarial drugs were lacking for periods ranging from 42 to138 days. The cross-sectional audit was even more negative, but here too the situation was more positive for anti-malarial drugs. The main reason for the shortage of drugs was insufficient deliveries from the Regional Medical Store. Benzyl penicillin was in shortest supply (4% received). The median value for non-availability was 240 days in the course of a year. The supply was better for anti-malarial drugs, except for quinine injections (9 %). Only 66 % of Stock Card records of quantities received were reflected in Patient Records showing quantities dispensed. Conclusion We conclude that for the eight index drugs the levels of supply are unacceptable. The main reason for the observed shortage of drugs at the health centres was insufficient deliveries from the Regional Medical Store. A difference between the information recorded on the Stock Cards at the health centres and that recorded in the Patient Records may have contributed to the overall poor drug supply situation. In order to ensure equitable access to life saving drugs, logistics in general should be put in order before specific disease management programmes are initiated.